Lithium transition metal oxide, positive electrode additive for lithium secondary battery, lithium secondary battery comprising the same
Patent Information
- Application Number
- KR1020210127489
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-27
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2041-09-27
Smart Images

Figure 112021110853364-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a lithium transition metal oxide, a positive electrode additive for a lithium secondary battery, and a lithium secondary battery comprising the same. Background Technology
[0003] As power consumption increases along with the multifunctionality of electronic devices, there are many attempts to increase the capacity of lithium-ion batteries and improve their charge and discharge efficiency.
[0004] For example, a technology has been proposed in which a cathode active material with 80% or more Ni is applied as a cathode material to the positive electrode of a lithium secondary battery, and a metal or metal-based negative electrode active material such as SiO, Si, or SiC is applied together with a carbon-based negative electrode active material such as natural graphite or artificial graphite to the negative electrode.
[0005] Metal and metal oxide-based cathode active materials enable the expression of higher capacity than carbon-based cathode active materials. However, because the volume change of metal and metal oxide-based cathode active materials during charging and discharging is much greater than that of graphite, it is difficult to increase the content of metal and metal oxide within the cathode to more than 15%. Furthermore, when metal and metal oxide are added to the cathode, irreversible reactions occur during the initial charging and discharging, resulting in greater lithium loss compared to the case where carbon-based cathode active materials are applied. Consequently, when metal and metal oxide-based cathode active materials are applied, the amount of lithium lost increases as the battery capacity increases, and the resulting decrease in initial capacity also becomes larger.
[0006] Accordingly, various methods have been studied to increase the capacity of lithium-ion batteries or reduce irreversible capacity. One of these is prelithiation, a concept that replenishes the lithium consumed in the formation of the SEI layer (solid electrolyte interphase layer) within the battery during the initial state.
[0007] Various methods have been proposed for pre-lithiation within batteries.
[0008] One example is a method of electrochemically lithiating the anode before operating the battery. However, the lithiated anode is very unstable in the atmosphere, and the electrochemical lithiation method is difficult to scale up the process.
[0009] As another example, lithium metal or lithium silicide (Li) on the cathode x This is a method for coating Si powder. However, since the above powder has high reactivity and reduced atmospheric stability, there is a problem in establishing suitable solvents and process conditions when coating the cathode.
[0010] One method for pre-lithiation at the cathode is to coat an additional amount of cathode material equivalent to the amount of lithium consumed at the anode. However, due to the inherently low capacity of the cathode material, the amount of additional material required increases, and consequently, the energy density and capacity per unit weight of the final battery decrease by the same amount.
[0011] Accordingly, materials suitable for the pre-lithiation of batteries at the cathode must possess irreversible characteristics, such as allowing at least twice as much lithium to be released compared to conventional cathode materials during the first charge, while remaining non-reactive with lithium during subsequent discharge. Additives that satisfy these conditions are called sacrificial positive electrode materials.
[0012] In the case of commercial batteries, after injecting the electrolyte into a case containing a stacked cathode, separator, and anode, the battery undergoes a formation process in which the first charge / discharge operation is performed. During this process, a reaction to form an SEI layer occurs on the anode, and gas is generated due to the decomposition of the electrolyte. In the aforementioned formation process, the sacrificial cathode material decomposes by releasing lithium and reacts with the electrolyte; the gases generated during this process, such as N2, O2, and CO2, are recovered through a gas pocket removal process.
[0013] Over-lithiated positive electrode materials, which are lithium-rich metal oxides, are widely used as the sacrificial cathode materials. Li6CoO4, Li5FeO4, and Li6MnO4, which have anti-fluorite structures, are well known as such over-lithiated positive electrode materials. Their theoretical capacities are 977 mAh / g for Li6CoO4, 867 mAh / g for Li5FeO4, and 1001 mAh / g for Li6MnO4, which are sufficient capacities for use as sacrificial cathode materials. Among them, Li6CoO4 has the best electrical conductivity and possesses good electrochemical properties for use as a sacrificial cathode material.
[0014] However, since the electrochemical structural stability of the sacrificial cathode material is insufficient due to its characteristics, structural collapse of the sacrificial cathode material occurs when an excess amount of lithium is defused and supplied to the anode to compensate for irreversible capacity loss during the initial charge-discharge process. Due to this structural collapse, a large amount of O2 gas is generated inside the cathode and the battery, which increases the pressure inside the battery and can significantly reduce the stability of the lithium secondary battery.
[0015] Due to the problems associated with these conventional sacrificial cathode materials, there is a continuous demand for the development of new cathode additives that can improve battery stability by suppressing gas generation during the lithium extraction process while exhibiting high irreversible capacity characteristics during the initial charging process. The problem to be solved
[0017] The present invention aims to provide a lithium transition metal oxide that exhibits a high initial irreversible capacity while suppressing gas generation during irreversible capacity loss compensation, thereby improving the stability of the battery.
[0018] The present invention is intended to provide a method for manufacturing the lithium transition metal oxide.
[0019] The present invention is to provide a positive electrode additive for a lithium secondary battery comprising the lithium transition metal oxide.
[0020] The present invention is to provide a positive electrode for a lithium secondary battery comprising the positive electrode additive for the lithium secondary battery.
[0021] In addition, the present invention is intended to provide a lithium secondary battery comprising a positive electrode for the secondary battery. means of solving the problem
[0023] According to one embodiment of the invention,
[0024] As a lithium (Li)-iron (Fe) oxide containing two or more different heterogeneous elements,
[0025] The above heterogeneous element is,
[0026] Aluminum (Al) and
[0027] One or more Group 2 elements selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn); and one or more elements selected from the group consisting of Group 13 elements selected from the group consisting of gallium (Ga) and indium (In), comprising
[0028] A lithium transition metal oxide is provided.
[0030] According to another embodiment of the invention,
[0031] A first step of mixing a lithium precursor, an iron precursor, and a heterogeneous element precursor; and
[0032] A second step of obtaining the lithium transition metal oxide by calcining the mixture obtained in the first step under an inert atmosphere and at a temperature of 500°C or higher.
[0033] A method for manufacturing a lithium transition metal oxide comprising is provided.
[0035] According to another embodiment of the invention,
[0036] A positive electrode additive for a lithium secondary battery comprising the above lithium transition metal oxide is provided.
[0038] According to another embodiment of the invention,
[0039] A positive electrode for a lithium secondary battery is provided, comprising a positive electrode active material, a binder, a conductive material, and a positive electrode additive for the lithium secondary battery.
[0041] According to another embodiment of the invention,
[0042] A lithium secondary battery is provided, comprising a positive electrode for the lithium secondary battery; a negative electrode; a separator; and an electrolyte.
[0044] Hereinafter, the lithium transition metal oxide, the method for manufacturing the lithium transition metal oxide, the cathode additive for a lithium secondary battery, the cathode for a lithium secondary battery, and the lithium secondary battery according to embodiments of the invention will be described in more detail.
[0046] Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical idea of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0047] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the invention pertains. The terms used in the description of the invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the invention.
[0048] The singular forms used in this specification include plural forms unless the phrases clearly indicate otherwise.
[0049] As used in this specification, the meaning of “includes” specifies certain characteristics, regions, integers, steps, actions, elements, and / or components, and does not exclude the existence or addition of other specific characteristics, regions, integers, steps, actions, elements, components, and / or groups.
[0050] The present invention is capable of various modifications and may take various forms, and specific embodiments are illustrated and described in detail below. However, this is not intended to limit the invention to the specific disclosed forms, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.
[0051] In this specification, where the positional relationship between two parts is described, for example, using expressions such as 'on', 'on the upper part', 'on the lower part', 'next to', etc., one or more other parts may be located between the two parts unless expressions such as 'immediately' or 'directly' are used.
[0052] In this specification, when temporal sequences are described, for example, using expressions such as ‘after,’ ‘following,’ ‘next,’ or ‘before,’ cases that are not continuous may be included unless expressions such as ‘immediately’ or ‘directly’ are used.
[0053] In this specification, the term 'at least one' should be understood to include all combinations that can be presented from one or more related items.
[0054] As used in this specification, the term “anode additive” refers to a material having irreversible characteristics in which lithium is extracted at least twice as much as in conventional cathode materials during the initial charging of a battery, and subsequently does not react with lithium during discharge. The anode additive may also be referred to as a sacrificial positive electrode material. Since the anode additive compensates for lithium loss, the capacity lost from the battery is restored, thereby increasing the battery's capacity. Furthermore, by suppressing gas generation, the battery's lifespan characteristics and safety can be improved by preventing the battery from exploding.
[0056] I. Lithium Transition Metal Oxides
[0058] According to one embodiment of the invention,
[0059] As a lithium (Li)-iron (Fe) oxide containing two or more different heterogeneous elements,
[0060] The above heterogeneous element is,
[0061] Aluminum (Al) and
[0062] One or more Group 2 elements selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn); and one or more elements selected from the group consisting of Group 13 elements selected from the group consisting of gallium (Ga) and indium (In), comprising
[0063] A lithium transition metal oxide is provided.
[0065] The inventors continued their research to develop a cathode additive, specifically a sacrificial cathode material, that can adequately compensate for irreversible capacity loss in high-capacity lithium secondary batteries while suppressing chemical and structural collapse during the irreversible capacity loss compensation process to suppress the generation of large amounts of oxygen gas.
[0066] The lithium transition metal oxide according to one embodiment is basically based on Li5FeO4, a previously known sacrificial cathode material, and it is known that such lithium transition metal oxide exhibits high irreversible capacity and capacity characteristics reaching approximately ~700 mAh / g during initial charging. However, it has been confirmed that during the irreversible capacity loss compensation process, this Li5FeO4-based cathode additive chemically and structurally collapses as excess lithium is defused, generating a large amount of oxygen gas.
[0067] To suppress such structural collapse, the lithium transition metal oxide of one embodiment comprises two or more different heterogeneous elements that are electrochemically inactive and can be alloyed with iron to form a stable single phase.
[0068] The above lithium transition metal oxide is a lithium (Li)-iron (Fe) oxide containing two or more different heterogeneous elements. The above lithium transition metal oxide contains aluminum (Al) as the main element among the heterogeneous elements. Furthermore, the above lithium transition metal oxide comprises: one or more Group 2 elements selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); and one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn). and one or more elements selected from the group consisting of Group 13 elements selected from the group consisting of gallium (Ga) and indium (In) are included as sub-elements among the heterogeneous elements.
[0069] Preferably, in terms of ease of alloying or doping with lithium (Li)-iron (Fe) oxide and stabilization of the crystal phase, the heterogeneous elements may include aluminum (Al) as the main element and one or more elements selected from the group consisting of magnesium (Mg), fluorine (F), titanium (Ti), zinc (Zn), and gallium (Ga) as sub-elements.
[0071] The above heterogeneous element may be included in an amount of 5 mol% to 50 mol% based on the total metal elements excluding lithium in the lithium (Li)-iron (Fe) oxide. Specifically, the above heterogeneous element may be included in an amount of 5 mol% or more, or 10 mol% or more, or 15 mol% or more, based on the total metal elements excluding lithium in the lithium (Li)-iron (Fe) oxide; and 50 mol% or less, or 40 mol% or less, or 30 mol% or less, or 25 mol% or less. Preferably, the above heterogeneous element may be included in an amount of 10 mol% to 50 mol%, or 10 mol% to 40 mol%, or 15 mol% to 40 mol%, or 15 mol% to 30 mol%, or 15 mol% to 25 mol% based on the total metal elements excluding lithium in the lithium (Li)-iron (Fe) oxide.
[0072] As the above heterogeneous element is included within the above content range, the lithium transition metal oxide can exhibit very high chemical and structural stability, and even after an excess amount of lithium is defused, structural collapse is suppressed and a chemically stable state is maintained. Accordingly, even after compensating for irreversible capacity loss during initial charging and discharging, the generation of oxygen gas within the cathode and the lithium secondary battery is suppressed, thereby significantly improving the stability of the high-capacity lithium secondary battery. Furthermore, as the above heterogeneous element is included within the above content range, the lithium transition metal oxide can exhibit high irreversible capacity and high capacity characteristics during initial charging, and as a result, irreversible capacity loss in the high-capacity battery can be sufficiently compensated.
[0073] However, if the content of the above heterogeneous element is too low, the lithium transition metal oxide may not be structurally stabilized sufficiently, and a large amount of oxygen gas may still be generated. Conversely, if the content of the above heterogeneous element is too high, the irreversible capacity and capacity characteristics of the lithium transition metal oxide may deteriorate, which is undesirable.
[0075] Furthermore, within the content range of the above heterogeneous elements, the content ratio of the main element (aluminum) and the sub-element (one or more elements selected from the group consisting of the above group 2 element, the above group 17 element, the above period 4 transition metal, and the above group 13 element) can be determined.
[0076] For example, among the above heterogeneous elements, aluminum (Al) may be included in an amount of 10 mol% to 35 mol% based on the total metal elements excluding lithium in the lithium (Li)-iron (Fe) oxide.
[0077] In order to enable the stabilization effect of the crystal phase to be expressed, it is preferable that the aluminum (Al) content in the lithium (Li)-iron (Fe) oxide be 10 mol% or more based on the total metal elements excluding lithium. However, if an excessive amount of heterogeneous elements is introduced, the electrical conductivity of the lithium transition metal oxide decreases, which may increase the resistance of the electrode and degrade the performance of the battery. Therefore, it is preferable that the aluminum (Al) content in the lithium (Li)-iron (Fe) oxide be 35 mol% or less based on the total metal elements excluding lithium.
[0078] Specifically, the content of aluminum (Al) in the lithium (Li)-iron (Fe) oxide may be 10 mol% or more, or 15 mol% or more, based on the total metal elements excluding lithium; and 35 mol% or less, or 30 mol% or less, or 25 mol% or less. Preferably, the content of aluminum (Al) in the lithium (Li)-iron (Fe) oxide may be 10 mol% to 30 mol%, or 10 mol% to 25 mol%, or 15 mol% to 25 mol%, based on the total metal elements excluding lithium.
[0080] The stabilization effect of the crystal phase of the above lithium transition metal oxide can be expected to be proportional to the content of the heterogeneous element. However, as the amount of heterogeneous element introduced, such as electrochemically inert aluminum (Al), increases, the initial charge capacity may relatively decrease and the electrical conductivity may show a tendency to decrease.
[0081] Therefore, it is preferable that the content of the sub-element among the above heterogeneous elements be 1 mol% or more based on the total metal elements excluding lithium. However, if an excessive amount of heterogeneous elements is introduced, the electrical conductivity of the lithium transition metal oxide decreases, the resistance of the electrode increases, and the performance of the battery may deteriorate. Therefore, it is preferable that the content of the sub-element in the lithium transition metal oxide be 10 mol% or less based on the total metal elements excluding lithium.
[0082] Specifically, the content of the sub-element among the heterogeneous elements in the lithium (Li)-iron (Fe) oxide may be 1 mol% or more, or 2 mol% or more, or 3 mol% or more, based on the total metal elements excluding lithium; and 10 mol% or less, or 7 mol% or less, or 5 mol% or less. Preferably, the content of the sub-element among the heterogeneous elements in the lithium (Li)-iron (Fe) oxide may be 1 mol% to 10 mol%, or 2 mol% to 10 mol%, or 2 mol% to 7 mol%, or 3 mol% to 7 mol%, or 3 mol% to 5 mol%, based on the total metal elements excluding lithium.
[0084] The above lithium (Li)-iron (Fe) oxide may be represented by the following chemical formula 1:
[0085] [Chemical Formula 1]
[0086] Li5Fe 1-x-y Al x M y O4
[0087] In the above chemical formula 1,
[0088] M is one or more Group 2 elements selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn); and one or more elements selected from the group consisting of Group 13 elements selected from the group consisting of gallium (Ga) and indium (In).
[0089] x is 0.1 to 0.35, and
[0090] y is 0.01 to 0.1.
[0092] Preferably, in the above formula 1, M may be one or more elements selected from the group consisting of magnesium (Mg), fluorine (F), titanium (Ti), zinc (Zn), and gallium (Ga).
[0094] In the above chemical formula 1, x is 0.1 to 0.35 and y is 0.01 to 0.1.
[0095] Specifically, the above x may be 0.10 or more, or 0.15 or more; and 0.35 or less, or 0.30 or less, or 0.25 or less. Preferably, the above x may be 0.10 to 0.35, or 0.15 to 0.35, or 0.15 to 0.30, or 0.15 to 0.25.
[0096] The above y may be 0.01 or more, or 0.02 or more, or 0.03 or more; and 0.10 or less, or 0.07 or less, or 0.05 or less. Preferably, the above y may be 0.01 to 0.1, or 0.02 to 0.1, or 0.02 to 0.07, or 0.03 to 0.07, or 0.03 to 0.05.
[0098] Preferably, the lithium (Li)-iron (Fe) oxide is Li5Fe 0.82 Al 0.15 Mg 0.03 O4, Li5Fe 0.77 Al 0.2 Mg 0.03 O4, Li5Fe 0.72 Al 0.25 Mg 0.03 O4, Li5Fe 0.81 Al 0.15 Mg 0.04 O4, Li5Fe 0.76 Al 0.2 Mg 0.04 O4, Li5Fe 0.71 Al 0.25 Mg 0.04 O4, Li5Fe 0.82 Al 0.15 F 0.03 O4, Li5Fe 0.77 Al 0.2 F 0.03 O4, Li5Fe 0.72 Al 0.25 F 0.03 O4, Li5Fe 0.81 Al 0.15 F 0.04 O4, Li5Fe 0.76 Al 0.2 F 0.04 O4, Li5Fe 0.71 Al 0.25 F 0.04 O4, Li5Fe 0.82 Al 0.15 Ti 0.03 O4, Li5Fe 0.77 Al 0.2 Ti 0.03 O4, Li5Fe 0.72 Al 0.25 Ti0.03 O4, Li5Fe 0.81 Al 0.15 Ti 0.04 O4, Li5Fe 0.76 Al 0.2 Ti 0.04 O4, Li5Fe 0.71 Al 0.25 Ti 0.04 O4, Li5Fe 0.82 Al 0.15 Zn 0.03 O4, Li5Fe 0.77 Al 0.2 Zn 0.03 O4, Li5Fe 0.72 Al 0.25 Zn 0.03 O4, Li5Fe 0.81 Al 0.15 Zn 0.04 O4, Li5Fe 0.76 Al 0.2 Zn 0.04 O4, Li5Fe 0.71 Al 0.25 Zn 0.04 O4, Li5Fe 0.82 Al 0.15 Ga 0.03 O4, Li5Fe 0.77 Al 0.2 Ga 0.03 O4, Li5Fe 0.72 Al 0.25 Ga 0.03 O4, Li5Fe 0.81 Al 0.15 Ga 0.04 O4, Li5Fe 0.76 Al 0.2 Ga 0.04 O4 and Li5Fe 0.71 Al 0.25 Ga 0.04 It may be one or more compounds selected from the group consisting of O4.
[0100] In the above lithium transition metal oxide, the heterogeneous element can form an alloy with iron (Fe) to exhibit a stable single phase. Due to the formation of this single phase, a portion of the lithium transition metal oxide is deactivated to ensure its structural stability, and the generation of a large amount of oxygen gas due to the decomposition of the lithium transition metal oxide can be suppressed.
[0101] The formation of a single phase alloyed with such heterogeneous elements can be confirmed, for example, by analyzing a transition metal oxide of one embodiment using XRD. Specifically, when the transition metal oxide is analyzed using XRD, a peak originating from iron (Fe) may appear as a single peak representing a stable single phase rather than a secondary phase as it shifts due to alloying.
[0102] In a specific example, the formation of a single phase alloyed with the heterogeneous element can be confirmed by the fact that a single peak derived from the iron (Fe), for example, at 2θ of 23° to 24°±0.1°, is shifted by about 0.10° to 0.20° compared to the case where the heterogeneous element is not added.
[0103] In contrast, if a secondary phase appears due to the inclusion of elements other than the aforementioned heterogeneous element, or if the formation of a single phase is insufficient because the heterogeneous element is not sufficiently included, XRD analysis results different from those of the lithium transition metal oxide of one embodiment may be obtained. For example, if the secondary phase is formed, peaks corresponding to Fe and the separate element may be identified as separated from each other in the XRD. Furthermore, if the formation of a single phase is insufficient because the heterogeneous element is not sufficiently included, the shift of the single peak may not be sufficiently observed compared to the lithium transition metal oxide of one embodiment. Since the lithium transition metal oxide of one embodiment contains the heterogeneous element in an alloyed state with a sufficient content ratio, a sufficient single peak shift can be confirmed in the XRD analysis results.
[0105] Meanwhile, the lithium transition metal oxide of one embodiment may consist of particles of the lithium (Li)-iron (Fe) oxide, but may further include a carbon nanotube-containing carbon composite additionally formed on the particles of the lithium (Li)-iron (Fe) oxide. Due to the additional formation of the carbon nanotube-containing carbon composite, the electrical conductivity of the lithium transition metal oxide is further enhanced, thereby exhibiting superior irreversible capacity and superior initial charge capacity characteristics.
[0106] The carbon composite may be included in an amount of 0.5 to 10.0 parts by weight, or 1.0 to 9.0 parts by weight, or 2.0 to 8.0 parts by weight, based on 100 parts by weight of the total content of the lithium (Li)-iron (Fe) oxide. Within the above content range, it is possible to improve electrical conductivity and irreversible capacity without degrading the basic properties of the lithium transition metal oxide.
[0107] The content range of the carbon nanotube-containing carbon composite can be measured and calculated by analyzing the carbon content contained on the surface of the lithium (Li)-iron (Fe) oxide particles through well-known element analysis or inductively coupled plasma (ICP) analysis, or based on the amount of carbon nanotubes used as raw materials.
[0109] Meanwhile, the lithium (Li)-iron (Fe) oxide particles may have the form of primary particles having a volume average particle size (D50) of 5 μm to 20 μm, 7 μm to 15 μm, or 9 μm to 13 μm, or secondary particles formed by the aggregation of primary particles, so that they can be uniformly mixed with the positive electrode active material and exhibit appropriate characteristics within the positive electrode. The volume average particle size (D50) of the lithium (Li)-iron (Fe) oxide particles can be measured and calculated using a well-known laser particle size analyzer, etc.
[0111] The above-described lithium transition metal oxide can be mixed with a separate positive electrode active material and act as a sacrificial positive electrode material to compensate for the irreversible capacity of the negative electrode during the initial charge / discharge process of a lithium secondary battery, and after such irreversible capacity compensation, the positive electrode active material can act.
[0113] II. Method for Manufacturing Lithium Transition Metal Oxides
[0115] According to another embodiment of the invention,
[0116] A first step of mixing a lithium precursor, an iron precursor, and a heterogeneous element precursor; and
[0117] A second step of obtaining the lithium transition metal oxide by calcining the mixture obtained in the first step under an inert atmosphere and at a temperature of 500°C or higher.
[0118] A method for manufacturing a lithium transition metal oxide comprising is provided.
[0120] In the first step above, a raw material mixture comprising a lithium precursor, an iron precursor, and a heterogeneous element precursor is prepared. The raw material mixture is prepared by solid-state mixing the lithium precursor, the iron precursor, and the heterogeneous element precursor to match the stoichiometric ratios described in "I. Lithium Transition Metal Oxides" above.
[0121] As the above lithium precursor, oxides containing lithium, such as Li2O, can be used without special limitations.
[0122] As the iron precursor, one or more compounds selected from the group consisting of Fe(III) chlorides, nitrates, sulfur oxides, phosphoric acids, oxides, halides, and hydrates thereof may be used.
[0123] The details regarding the above heterogeneous elements are replaced by the contents described in the above section “I. Lithium Transition Metal Oxides.” The above heterogeneous elements may include one or more Group 2 elements selected from the group consisting of aluminum (Al); magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn); and one or more elements selected from the group consisting of one or more Group 13 elements selected from the group consisting of gallium (Ga) and indium (In).
[0124] As the heterogeneous element precursor, an oxide or ammonium salt of the heterogeneous element may be used. As a non-limiting example, compounds such as Al2O3, NH4F, TiO2, MgO, ZnO, and Ga2O3 may be used as the heterogeneous element precursor.
[0126] In the second step above, the lithium transition metal oxide is obtained by calcining the raw material mixture obtained in the first step under an inert atmosphere and at a temperature of 500°C or higher.
[0127] The above second step can be performed under an inert atmosphere formed using inert gases such as Ar, N2, Ne, and He.
[0128] The calcination in the second step above may be performed at a temperature of 500 ℃ or higher, or between 500 ℃ and 1000 ℃, or between 550 ℃ and 800 ℃. In order to generate crystal seeds at an appropriate rate, it is preferable that the calcination temperature be 500 ℃ or higher, or 550 ℃ or higher. However, if the calcination temperature is excessively high, sintering may occur in which the grown crystal grains clump together. Therefore, it is preferable that the calcination temperature be 1000 ℃ or lower, or 800 ℃ or lower. Specifically, the calcination temperature may be 500 ℃ or higher, or 550 ℃ or higher, or 600 ℃ or higher; and 1000 ℃ or lower, or 800 ℃ or lower, or 700 ℃ or lower. Preferably, the firing temperature may be 550 ℃ to 1000 ℃, or 550 ℃ to 800 ℃, or 550 ℃ to 700 ℃, or 600 ℃ to 700 ℃.
[0129] The above sintering may be performed for 2 to 12 hours at the above sintering temperature. The above sintering time may be adjusted by taking into account the time required for the crystal to stabilize after the heterogeneous element is introduced into the lithium-iron oxide in the form of an alloy. Specifically, the above sintering time may be 2 hours or more, or 3 hours or more, or 4 hours or more; and 12 hours or less, or 11 hours or less, or 10 hours or less. Preferably, the above sintering time may be 3 to 12 hours, or 3 to 11 hours, or 4 to 11 hours, or 4 to 10 hours.
[0131] In a specific example, the method for manufacturing the lithium transition metal oxide may be performed by including the steps of: mixing and heat-treating a carbon nanotube and an iron precursor to form an iron oxide-carbon nanotube precursor; and mixing a lithium precursor, a heterogeneous element precursor, and the iron oxide-carbon nanotube precursor and calcining at a temperature of 500°C or higher.
[0132] In the above manufacturing method, an iron precursor and a carbon nanotube are first mixed and reacted to produce an iron oxide-carbon nanotube precursor, and then mixed with a lithium precursor and a heterogeneous element precursor and calcined at high temperature, thereby producing a lithium transition metal oxide in which a carbon nanotube-containing carbon composite is formed on the particles of lithium (Li)-iron (Fe) oxide.
[0133] More specifically, the step of forming the iron oxide-carbon nanotube precursor may be performed by including the step of mixing the carbon nanotube and the iron (Fe) precursor; the step of reacting the carbon nanotube and the iron (Fe) precursor at a temperature of 50 ℃ to 100 ℃ in the presence of a base such as sodium hydroxide or ammonium hydroxide; and the step of heat-treating the reaction product at a temperature of 200 ℃ to 300 ℃.
[0134] In order to form a carbon composite with an appropriate amount, the carbon nanotubes may be used in an amount of 0.3 moles to 15.0 parts by weight, or 1.0 parts by weight to 10.0 parts by weight, or 2.0 parts by weight to 8.0 parts by weight, based on 1 mole of the iron (Fe) precursor mixed therewith.
[0135] After mixing the carbon nanotube and iron precursor, the carbon nanotube and iron precursor may be reacted at a temperature of 50°C to 100°C or 70°C to 90°C for, for example, 1 hour to 10 hours; and further heat-treated at a temperature of 200°C to 300°C or 220°C to 280°C for 2 hours to remove impurities. An iron oxide-carbon nanotube precursor may be formed by this process.
[0137] If necessary, a step of cleaning and drying the lithium transition metal oxide obtained in the second step may be performed. As a non-limiting example, the cleaning process may be performed by mixing and stirring the lithium transition metal oxide and the cleaning solution in a weight ratio of 1:2 to 1:10. Distilled water, ammonia water, etc., may be used as the cleaning solution. The drying may be performed by heat treatment at a temperature of 100°C to 200°C or 100°C to 180°C for 1 hour to 10 hours.
[0139] III. Cathode Additives for Lithium Secondary Batteries
[0141] According to another embodiment of the invention,
[0142] A positive electrode additive for a lithium secondary battery comprising the above lithium transition metal oxide is provided.
[0144] The above lithium transition metal oxide exhibits a high initial irreversible capacity, while suppressing gas generation during irreversible capacity loss compensation, thereby improving the stability of the battery.
[0145] The cathode additive for a lithium secondary battery comprising the above-mentioned lithium transition metal oxide has the characteristic of irreversibly releasing lithium during the charging and discharging of the lithium secondary battery. Therefore, the above-mentioned cathode additive for a lithium secondary battery can be included in the cathode of a lithium secondary battery and perform the role of a sacrificial positive electrode material for prelithiation.
[0147] Matters concerning the above lithium transition metal oxides are replaced by the contents described in item 『I. Lithium Transition Metal Oxides』 above.
[0149] The above lithium transition metal oxide is a lithium (Li)-iron (Fe) oxide containing two or more different heterogeneous elements. The above lithium transition metal oxide contains aluminum (Al) as the main element among the heterogeneous elements. Furthermore, the above lithium transition metal oxide comprises: one or more Group 2 elements selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); and one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn). and one or more elements selected from the group consisting of Group 13 elements selected from the group consisting of gallium (Ga) and indium (In) are included as sub-elements among the heterogeneous elements.
[0150] Preferably, in terms of ease of alloying or doping with lithium (Li)-iron (Fe) oxide and stabilization of the crystal phase, the heterogeneous elements may include aluminum (Al) as the main element and one or more elements selected from the group consisting of magnesium (Mg), fluorine (F), titanium (Ti), zinc (Zn), and gallium (Ga) as sub-elements.
[0151] The above heterogeneous element may be included in an amount of 5 mol% to 50 mol% based on the total metal elements excluding lithium in the above lithium (Li)-iron (Fe) oxide.
[0152] Among the above heterogeneous elements, aluminum (Al) may be included in an amount of 10 mol% to 35 mol% based on the total metal elements excluding lithium in the lithium (Li)-iron (Fe) oxide. Among the above heterogeneous elements, the content of the above sub-element may be included in an amount of 1 mol% to 10 mol% based on the total metal elements excluding lithium.
[0154] The above lithium (Li)-iron (Fe) oxide may be represented by the following chemical formula 1:
[0155] [Chemical Formula 1]
[0156] Li5Fe 1-x-y Al x M y O4
[0157] In the above chemical formula 1,
[0158] M is one or more Group 2 elements selected from the group consisting of magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); one or more Group 17 elements selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); one or more Period 4 transition metals selected from the group consisting of scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), cobalt (Co), copper (Cu), and zinc (Zn); and one or more elements selected from the group consisting of Group 13 elements selected from the group consisting of gallium (Ga) and indium (In).
[0159] x is 0.1 to 0.35, and
[0160] y is 0.01 to 0.1.
[0162] Preferably, in the above formula 1, M may be one or more elements selected from the group consisting of magnesium (Mg), fluorine (F), titanium (Ti), zinc (Zn), and gallium (Ga).
[0164] Preferably, the lithium (Li)-iron (Fe) oxide is Li5Fe 0.82 Al 0.15 Mg 0.03 O4, Li5Fe 0.77 Al 0.2 Mg 0.03 O4, Li5Fe 0.72 Al 0.25 Mg 0.03 O4, Li5Fe 0.81 Al 0.15 Mg 0.04 O4, Li5Fe 0.76 Al 0.2 Mg 0.04 O4, Li5Fe 0.71 Al 0.25 Mg 0.04 O4, Li5Fe 0.82 Al 0.15 F 0.03 O4, Li5Fe 0.77 Al 0.2 F 0.03O4, Li5Fe 0.72 Al 0.25 F 0.03 O4, Li5Fe 0.81 Al 0.15 F 0.04 O4, Li5Fe 0.76 Al 0.2 F 0.04 O4, Li5Fe 0.71 Al 0.25 F 0.04 O4, Li5Fe 0.82 Al 0.15 Ti 0.03 O4, Li5Fe 0.77 Al 0.2 Ti 0.03 O4, Li5Fe 0.72 Al 0.25 Ti 0.03 O4, Li5Fe 0.81 Al 0.15 Ti 0.04 O4, Li5Fe 0.76 Al 0.2 Ti 0.04 O4, Li5Fe 0.71 Al 0.25 Ti 0.04 O4, Li5Fe 0.82 Al 0.15 Zn 0.03 O4, Li5Fe 0.77 Al 0.2 Zn 0.03 O4, Li5Fe 0.72 Al 0.25 Zn 0.03 O4, Li5Fe 0.81 Al 0.15 Zn 0.04 O4, Li5Fe 0.76 Al 0.2 Zn 0.04 O4, Li5Fe 0.71 Al 0.25 Zn 0.04 O4, Li5Fe 0.82 Al 0.15 Ga 0.03 O4, Li5Fe 0.77 Al 0.2 Ga 0.03 O4, Li5Fe 0.72 Al 0.25 Ga 0.03 O4, Li5Fe0.81 Al 0.15 Ga 0.04 O4, Li5Fe 0.76 Al 0.2 Ga 0.04 O4 and Li5Fe 0.71 Al 0.25 Ga 0.04 It may be one or more compounds selected from the group consisting of O4.
[0166] IV. Cathode for Lithium Secondary Batteries
[0168] According to another embodiment of the invention, a positive electrode for a lithium secondary battery is provided.
[0169] The positive electrode for the lithium secondary battery described above may include a positive electrode active material, a binder, a conductive material, and the lithium transition metal oxide.
[0170] The above lithium transition metal oxide and the above cathode additive for a lithium secondary battery have the characteristic of irreversibly releasing lithium during the charging and discharging of the lithium secondary battery. Therefore, the above lithium transition metal oxide and the above cathode additive for a lithium secondary battery can be included in the cathode of a lithium secondary battery and perform the role of sacrificial positive electrode materials for prelithiation.
[0172] Preferably, the positive electrode for the lithium secondary battery comprises a positive electrode active material, a conductive material, the sacrificial positive electrode material, and a binder; and a current collector that supports the positive electrode material.
[0174] Here, the sacrificial cathode material is the lithium transition metal oxide. Details regarding the sacrificial cathode material are substituted with the contents described in the items of 『I. Lithium Transition Metal Oxides』 and 『III. Cathode Additives for Lithium Secondary Batteries』.
[0176] As the capacity of the battery increases, the proportion of the negative electrode active material in the negative electrode must be increased to increase the battery capacity, and accordingly, the amount of lithium consumed in the SEI layer also increases. Therefore, the design capacity of the battery can be determined by calculating the amount of lithium consumed in the SEI layer of the negative electrode and then inversely calculating the amount of sacrificial cathode material to be applied to the positive electrode.
[0177] According to one embodiment, the sacrificial cathode material may be included in an amount greater than 0 weight% and less than or equal to 15 weight% relative to the total weight of the cathode material.
[0178] In order to compensate for the irreversible lithium consumed in the formation of the SEI layer, it is preferable that the content of the sacrificial cathode material be greater than 0 weight% relative to the total weight of the cathode material.
[0179] However, if the sacrificial cathode material is included in excess, the content of the cathode active material exhibiting reversible charge / discharge capacity decreases, thereby reducing the capacity of the battery, and residual lithium within the battery may be plated onto the negative electrode, causing a short circuit in the battery or compromising safety. Therefore, it is preferable that the content of the sacrificial cathode material be 15 weight% or less relative to the total weight of the cathode material.
[0180] Specifically, the content of the sacrificial cathode material may be greater than 0 weight%, or 0.5 weight% or more, or 1 weight% or more, or 2 weight% or more, or 3 weight% or more relative to the total weight of the cathode material; and, 15 weight% or less, or 12 weight% or less, or 10 weight% or less.
[0181] Preferably, the content of the sacrificial cathode material may be 0.5% to 15% by weight, or 1% to 15% by weight, or 1% to 12% by weight, or 2% to 12% by weight, or 2% to 10% by weight, or 3% to 10% by weight, relative to the total weight of the cathode material.
[0183] As the above-mentioned positive electrode active material, any material capable of reversible insertion and extraction of lithium ions may be used without special limitations. For example, the above-mentioned positive electrode active material may be a complex oxide or phosphate containing lithium and metals such as cobalt, manganese, nickel, iron, or a combination thereof.
[0184] As a non-limiting example, the positive active material may be a compound represented by any one of the following chemical formulas.
[0185] Li a A 1-b R b D2(0.90≤a≤1.8, 0≤b≤0.5); Li a E 1-b R b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2-b R b O 4-c D c (0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b R c D d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d≤2); Li a Ni 1-b-c Co b R c O 2-d Z d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni 1-b-c Co b R c O 2-d Z2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni 1-b-c Mn b R c D d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d≤2); Li a Ni 1-b-c Mnb R c About 2-d Z d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni 1-b-c Mn b R c About 2-d Z2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni b E c G d O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1.); Li a Ni b Co c Mn d G e O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NiG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G b O4(0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2); Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.
[0186] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0187] Of course, a coating layer on the surface of the above-mentioned positive active material may be used, or a mixture of the above-mentioned positive active material and the positive active material having a coating layer may be used. As coating elements included in the above-mentioned coating layer, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof may be used.
[0188] According to one embodiment, the positive active material may be included in an amount of 80% to 95% by weight relative to the total weight of the positive material.
[0189] Specifically, the content of the positive electrode active material may be 80 weight% or more, or 82 weight% or more, or 85 weight% or more relative to the total weight of the positive electrode material; and, 95 weight% or less, or 93 weight% or less, or 90 weight% or less.
[0190] Preferably, the content of the positive active material may be 82% to 95% by weight, or 82% to 93% by weight, or 85% to 93% by weight, or 85% to 90% by weight, relative to the total weight of the positive material.
[0192] The above conductive material is used to impart conductivity to the electrode.
[0193] The above conductive material may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes in the battery. As a non-limiting example, the above conductive material may be carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber; graphite such as natural graphite or artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive polymers such as polyphenylene derivatives. As the above conductive material, one or more of the examples described above may be used.
[0194] The content of the conductive material can be adjusted within a range that does not cause a reduction in battery capacity while exhibiting an appropriate level of conductivity. Preferably, the content of the conductive material may be 1% to 10% by weight or 1% to 5% by weight relative to the total weight of the cathode material.
[0196] The above binder is used to properly attach the above anode material to the above current collector.
[0197] As a non-limiting example, the binder may be polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc. As the binder, one or more of the examples described above may be used.
[0198] The content of the binder can be adjusted within a range that does not cause a reduction in battery capacity while exhibiting an appropriate level of adhesion. Preferably, the content of the binder may be 1% to 10% by weight or 1% to 5% by weight relative to the total weight of the cathode material.
[0200] As the above current collector, any material known to be applicable to the positive electrode of a lithium secondary battery in the technical field to which the present invention belongs may be used without special limitations.
[0201] As a non-limiting example, the above current collector may be stainless steel; aluminum; nickel; titanium; calcined carbon; or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc.
[0202] Preferably, the current collector may have a thickness of 3 μm to 500 μm. In order to increase the adhesion of the anode material, the current collector may have fine irregularities formed on its surface. The current collector may have various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0204] The positive electrode for the lithium secondary battery can be formed by laminating a positive electrode material comprising the positive electrode active material, the conductive material, the sacrificial positive electrode material, and a binder onto the current collector.
[0206] V. Lithium Secondary Battery
[0208] According to another embodiment of the invention,
[0209] A lithium secondary battery is provided, comprising a positive electrode for the lithium secondary battery; a negative electrode; a separator; and an electrolyte.
[0211] The above lithium secondary battery comprises a cathode comprising the lithium transition metal oxide or the cathode additive for the lithium secondary battery. Accordingly, the lithium secondary battery can suppress gas generation in the charging and discharging cathode and exhibit improved safety and lifespan characteristics. Furthermore, the lithium secondary battery can exhibit high discharge capacity, excellent output characteristics, and capacity retention rate.
[0213] Accordingly, the lithium secondary battery can be used as an energy source with enhanced performance and safety in the field of portable electronic devices such as mobile phones, laptop computers, tablet computers, mobile batteries, and digital cameras; and in the field of means of transportation such as electric vehicles, electric motorcycles, and personal mobility devices.
[0215] The above lithium secondary battery may include an electrode assembly wound with a separator interposed between a positive electrode and a negative electrode, and a case in which the electrode assembly is housed. Additionally, the positive electrode, the negative electrode, and the separator may be impregnated with an electrolyte.
[0217] The above lithium secondary battery can have various shapes, such as prismatic, cylindrical, and pouch types.
[0219] Matters concerning the above-mentioned anode are replaced by the contents described in item 『IV. Anode for Lithium Secondary Battery』 above.
[0221] The above cathode may include a cathode material comprising a cathode active material, a conductive material, and a binder; and a current collector supporting the cathode material.
[0223] The above-mentioned negative electrode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0224] Examples of materials capable of reversibly intercalating and deintercalating the above lithium ions include carbonaceous materials such as crystalline carbon, amorphous carbon, or mixtures thereof. Specifically, the carbonaceous materials may be natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitches, mesophase pitch-based carbon fibers, meso-carbon microbeads, petroleum or coal tar pitch-derived cokes, soft carbon, and hard carbon.
[0225] The above lithium metal alloy may be an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.
[0226] The materials capable of doping and dedoping the above lithium are Si, Si-C complexes, SiOx (0 <x<2), Si-Q 합금(상기 Q는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 15족 원소, 16족 원소, 전이 금속, 희토류 원소, 및 이들의 조합으로 이루어진 군에서 선택되는 원소이다; 단, Si는 제외한다), Sn, SnO2, Sn-R 합금(상기 R은 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 15족 원소, 16족 원소, 전이 금속, 희토류 원소, 및 이들의 조합으로 이루어진 군에서 선택되는 원소이다; 단, Sn은 제외한다.) 등일 수 있다. 그리고, 상기 리튬에 도프 및 탈도프 가능한 물질로는 상기 예들 중 적어도 하나와 SiO2를 혼합하여 사용할 수 있다. 상기 Q 및 R은 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po 등일 수 있다.
[0227] And, the above transition metal oxide may be vanadium oxide, lithium vanadium oxide, lithium titanium oxide, etc.
[0229] Preferably, the cathode may include one or more cathode active materials selected from the group consisting of carbonaceous materials and silicon compounds.
[0230] That is, according to another embodiment of the invention, a lithium secondary battery is provided comprising: a positive electrode for the lithium secondary battery; a negative electrode comprising one or more negative active materials selected from the group consisting of carbonaceous materials and silicon compounds; a separator; and an electrolyte.
[0231] Here, the carbonaceous material is one or more materials selected from the group consisting of natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fibers, carbon microspheres, petroleum or coal-based coke, softened carbon, and hardened carbon, as previously exemplified. And, the silicon compound is a compound containing Si as previously exemplified, namely Si, Si-C complexes, SiOx (0 <x<2), 상기 Si-Q 합금, 이들의 혼합물, 또는 이들 중 적어도 하나와 SiO2의 혼합물일 수 있다.
[0233] According to one embodiment, the negative electrode active material may be included in an amount of 85% to 98% by weight relative to the total weight of the negative electrode material.
[0234] Specifically, the content of the cathode active material may be 85 weight% or more, or 87 weight% or more, or 90 weight% or more relative to the total weight of the cathode material; and, 98 weight% or less, or 97 weight% or less, or 95 weight% or less.
[0235] Preferably, the content of the cathode active material may be 85% to 97% by weight, or 87% to 97% by weight, or 87% to 95% by weight, or 90% to 95% by weight, relative to the total weight of the cathode material.
[0237] The conductive material, the binder, and the current collector included in the above-mentioned cathode material are described in accordance with the contents of item 『IV. Cathode for Lithium Secondary Battery』 above.
[0239] The above-mentioned separator separates the positive and negative electrodes and provides a pathway for the movement of lithium ions. Any separator known in the art to which the present invention belongs to be applicable to a separator of a lithium secondary battery may be used without any particular limitations. It is preferable that the separator has low resistance to the movement of electrolyte ions and excellent wettability to the electrolyte.
[0240] Specifically, the separator may be a porous polymer film made of a polyolefin-based polymer such as polyethylene, polypropylene, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-methacrylate copolymer, etc. The separator may be a multilayer film in which the porous polymer film is laminated in two or more layers. The separator may be a nonwoven fabric including glass fibers, polyethylene terephthalate fibers, etc. Additionally, the separator may be coated with a ceramic component or a polymer material to ensure heat resistance or mechanical strength.
[0242] Meanwhile, the above electrolyte may be used without special limitations as long as it is known to be applicable to lithium secondary batteries in the technical field to which the present invention belongs. For example, the above electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.
[0244] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt.
[0246] The above-mentioned non-aqueous organic solvent can be used without special restrictions as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move.
[0247] Specifically, the non-aqueous organic solvent is an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; an ether-based solvent such as dibutyl ether and tetrahydrofuran; a ketone-based solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene and fluorobenzene; and a carbonate-based solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC). Alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having C2 to C20 and may include a double bond, directional ring, or ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes, etc.
[0249] Among the above examples, a carbonate-based solvent may preferably be used as the above-mentioned non-aqueous organic solvent.
[0250] In particular, considering the charge / discharge performance of the battery and compatibility with the sacrificial cathode material, a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant (e.g., ethylene carbonate, propylene carbonate) and a linear carbonate having low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate) may preferably be used as the non-aqueous organic solvent. In this case, using a mixture of the cyclic carbonate and the linear carbonate in a volume ratio of 1:1 to 1:9 may be advantageous for exhibiting the aforementioned performance.
[0251] In addition, the above-mentioned non-aqueous organic solvent may preferably be a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 to 1:10; or a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1 to 3:1 to 9:1.
[0253] The lithium salt included in the above electrolyte is dissolved in the above-mentioned non-aqueous organic solvent and acts as a source of lithium ions within the battery, enabling the operation of a basic lithium secondary battery and facilitating the movement of lithium ions between the positive and negative electrodes.
[0254] Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiN(SO2F)2 (LiFSI, lithium bis(fluorosulfonyl)imide), LiCl, LiI, and LiB(C2O4)2, etc. Preferably, the lithium salt may be LiPF6, LiFSI, and mixtures thereof.
[0255] The lithium salt may be included in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt included in the above concentration range enables excellent electrolyte performance by imparting appropriate conductivity and viscosity to the electrolyte.
[0257] Optionally, the electrolyte may include additives intended for improving the lifespan characteristics of the battery, suppressing the reduction of battery capacity, and improving the discharge capacity of the battery.
[0258] For example, the above additive may be a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The above additive may be included in an amount of 0.1% to 5% by weight based on the total weight of the electrolyte. Effects of the invention
[0260] The lithium transition metal oxide according to the present invention exhibits a high initial irreversible capacity, while suppressing gas generation during irreversible capacity loss compensation, thereby improving the stability of the battery.
[0261] These lithium transition metal oxides can compensate for irreversible capacity loss in high-capacity lithium secondary batteries, while effectively suppressing gas generation in the battery and the resulting fires and explosions. Brief explanation of the drawing
[0263] Figures 1 and 2 are the results of X-ray diffraction (XRD) analysis of lithium transition metal oxides formed in Examples 1 to 6 and Comparative Examples 1 and 2, respectively. Figures 3 to 6 are the results of EDS mapping analysis for lithium transition metal oxides formed in Examples 1 and 2 and Comparative Examples 1 and 2, respectively. Specific details for implementing the invention
[0264] The operation and effects of the invention will be explained in more detail through the specific embodiments described below. However, these are presented merely as examples to aid in understanding the invention. The following embodiments are not intended to limit the scope of the invention in any way, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the invention.
[0266] Example 1
[0267] (1) Synthesis of lithium transition metal oxides
[0268] 0.6 mol of FeCl2 as an Fe precursor and 5 wt% of carbon nanotubes were mixed, then 1.8 mol of NaOH was added and the mixture was reacted at 80 °C for 6 hours and dried. Subsequently, an iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) was synthesized by removing impurities through heat treatment at 250 °C for 6 hours under an air atmosphere.
[0269] 20 mol% of Al2O3 and 3 mol% of NH4F were added relative to the above Fe2O3@CNT precursor, mixed with Li2O at a molar ratio of 1:5, and then calcined at 600 ℃ for 6 hours under an argon atmosphere to obtain a lithium transition metal oxide (Li5Fe 0.77 Al 0.2 F 0.03 O4) was manufactured.
[0271] (2) Manufacturing of lithium secondary batteries
[0272] A cathode material slurry was prepared by mixing the above lithium transition metal oxide, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder in an organic solvent (N-methylpyrrolidone) in a weight ratio of 95:2:3. The cathode material slurry was applied to one side of a current collector, which is an aluminum foil with a thickness of 15 μm, and then rolled and dried to produce a cathode.
[0273] After configuring an electrode assembly with the above-mentioned positive electrode, negative electrode, and separator, the electrode assembly was housed in a pouch to form a small cell, and an electrolyte was injected into the pouch to fabricate a lithium secondary battery monocell.
[0274] At this time, a Li-metal with a thickness of 300 μm (stamping size: Φ14 mm) was used as the cathode. As the electrolyte, 1.0 M LiPF6 and 2 wt% vinylene carbonate (VC) were dissolved in a non-aqueous organic solvent mixed with ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) in a volume ratio of 1:2:1. And, as the separator, a PE resin separator (manufactured by W-scope, WL20C, 20 μm) was used.
[0276] Example 2
[0277] An iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) according to Example 1 above was synthesized. 20 mol% of Al2O3 and 3 mol% of TiO2 were added relative to the Fe2O3@CNT precursor, mixed with Li2O at a molar ratio of 1:5, and then calcined at 600 °C for 6 hours under an argon atmosphere to produce a lithium transition metal oxide (Li5Fe 0.77 Al 0.2 Ti 0.03 O4) was manufactured. Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1.
[0279] Example 3
[0280] An iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) according to Example 1 above was synthesized. 20 mol% of Al2O3 and 3 mol% of MgO were added relative to the Fe2O3@CNT precursor, mixed with Li2O at a molar ratio of 1:5, and then calcined at 600 °C for 6 hours under an argon atmosphere to produce a lithium transition metal oxide (Li5Fe 0.77 Al 0.2 Mg 0.03 O4) was manufactured. Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1.
[0282] Example 4
[0283] An iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) according to Example 1 above was synthesized. 20 mol% of Al2O3 and 3 mol% of ZnO were added relative to the Fe2O3@CNT precursor, mixed with Li2O at a molar ratio of 1:5, and then calcined at 600 °C for 6 hours under an argon atmosphere to produce a lithium transition metal oxide (Li5Fe 0.77 Al 0.2 Zn 0.03 O4) was manufactured. Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1.
[0285] Example 5
[0286] An iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) according to Example 1 above was synthesized. 20 mol% of Al2O3 and 3 mol% of Ga2O3 were added relative to the Fe2O3@CNT precursor, mixed with Li2O at a molar ratio of 1:5, and then calcined at 600 °C for 6 hours under an argon atmosphere to produce a lithium transition metal oxide (Li5Fe 0.77 Al 0.2 Ga0.03 O4) was manufactured. Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1.
[0288] Example 6
[0289] A lithium transition metal oxide (Li5Fe) was prepared in the same manner as in Example 1, except that 25 mol% of Al2O3 and 5 mol% of TiO2 were added relative to the above Fe2O3@CNT precursor. 0.70 Al 0.25 Ti 0.05 O4) was manufactured. Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1.
[0291] Comparative Example 1
[0292] An iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) according to Example 1 above was synthesized. 20 mol% of Al2O3 was added relative to the Fe2O3@CNT precursor, mixed with Li2O at a molar ratio of 1:5, and then calcined at 600 °C for 6 hours under an argon atmosphere to produce a lithium transition metal oxide (Li5Fe 0.8 Al 0.2 O4) was manufactured. Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1.
[0294] Comparative Example 2
[0295] An iron oxide-carbon nanotube precursor (Fe2O3@CNT precursor) according to Example 1 above was synthesized. The Fe2O3@CNT precursor and Li2O were mixed in a molar ratio of 1:5, and then calcined at a temperature of 600 °C for 6 hours under an argon atmosphere to produce a lithium transition metal oxide (Li5FeO4). Then, a lithium secondary battery was manufactured using the lithium transition metal oxide in the same manner as in Example 1 above.
[0297] Experimental Example 1
[0298] XRD analysis was performed on the lithium transition metal oxides prepared in Examples 1 to 6 and Comparative Examples 1 and 2 using an XRD analysis instrument (D8 Endeavor, manufactured by Bruker).
[0299] XRD analysis results for lithium transition metal oxides of Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Figures 1 and 2.
[0300] Referring to FIG. 1, in the lithium transition metal oxides of Examples 1 to 6, the formation of a Li5FeO4 single phase was confirmed even after alloying with Al and various heterogeneous metal elements. In addition, no particular peak shift was observed when comparing Examples 1 to 6, which were alloyed in the same ratio.
[0301] Referring to FIG. 2, in Example 6, Comparative Example 1, and Comparative Example 2, which have different alloying ratios, the formation of a Li5FeO4 single phase was confirmed, but a peak shift was observed. In Comparative Example 1, a relatively larger peak shift was confirmed compared to Comparative Example 2, and in Example 6, a relatively larger peak shift was confirmed compared to Comparative Example 1.
[0302] This single peak was shifted by about 0.15° 2θ compared to the previously known corresponding peak of Li5FeO4 itself, for example, the peak identified at 2θ of 23° to 24°±0.1°. Through this, it can be confirmed that a single phase stably alloyed was formed even when the ratio of Al and heterogeneous metal elements increased.
[0304] Experimental Example 2
[0305] The distribution of iron (Fe), aluminum (Al), fluorine (F), titanium (Ti), and oxygen (O) elements in the lithium transition metal oxides prepared in Examples 1 and 2 and Comparative Examples 1 and 2 was confirmed using an SEM-EDS instrument (JSM7610F, manufactured by JEOL), and the results are shown in Fig. 3 (Example 1), Fig. 4 (Example 2), Fig. 5 (Comparative Example 1), and Fig. 6 (Comparative Example 2).
[0306] Referring to Figures 3 and 4, in Examples 1 and 2, it can be seen that the aluminum element and the fluorine or titanium element are evenly distributed throughout the lithium transition metal oxide particles. As fluorine and titanium are doped in very small amounts, the EDS intensity is very weak.
[0307] On the other hand, referring to Fig. 6, it was confirmed that in Comparative Example 2, aluminum elements were not distributed and the lithium transition metal oxide particles were composed of iron and oxygen elements.
[0309] Experimental Example 3
[0310] Quantitative analysis of lithium (Li), iron (Fe), aluminum (Al), fluorine (F), and titanium (Ti) elements was performed on the lithium transition metal oxides prepared in Examples 1 and 6 and Comparative Examples 1 and 2 using an ICP-MS instrument (7900 ICP-MS, manufactured by Agilent), and the molar ratio of Li : Fe : Al : (F or Ti) was calculated.
[0311] Li Fe Al F Ti Example 1 5.0 0.77 0.20 0.03 - Example 6 5.0 0.70 0.25 - 0.05 Comparative Example 1 5.0 0.80 0.20 - - Comparative Example 2 5.0 1.00 - - -
[0313] Experimental Example 4
[0314] For the lithium transition metal oxides prepared in Examples 1 to 6 and Comparative Examples 1 and 2, the D50 value was measured using a laser diffraction particle size analyzer (s3500, manufactured by Microtrac).
[0315] D50 (㎛) CNT content (weight%) Heterogeneous elements (molar ratio) Example 1 10.5 3.5 Al 0.20; F 0.03 Example 2 9.3 3.5 Al 0.20; Ti 0.03 Example 3 9.5 3.5 Al 0.20; Mg 0.03 Example 4 11.0 3.5 Al 0.20; Zn 0.03 Example 5 9.7 3.5 Al 0.20; Ga 0.03 Example 6 9.0 3.5 Al 0.25; Ti 0.05 Comparative Example 1 9.4 3.5 Al 0.20 Comparative Example 2 10.2 3.5 -
[0317] Experimental Example 5
[0318] (1) Measurement of Formation (Initial Charge) Capacity and Charge / Discharge Capacity
[0319] The above monocell was charged at 0.1 C in CC-CV mode at 45°C until it reached 4.25 V, and the voltage was maintained in CV mode until it reached 0.05 C. Subsequently, a charge-discharge experiment was conducted by discharging at 0.1 C to 2.5 V. Through the above charge-discharge experiment, the formation (initial charge) capacity and charge-discharge capacity were measured.
[0321] (2) Measurement of accumulated gas generation amount due to accumulated charge / discharge
[0322] Using a hydrometer (MATSUHAKU, TWD-150DM), the difference between the original weight of the monocell and its weight in water was measured, and the change in volume within the monocell was calculated. The amount of gas generated per unit weight was calculated by dividing the change in volume by the weight of the electrode active material.
[0324] (3) Measurement of accumulated gas generation due to high-temperature storage
[0325] The monocell was charged at 0.1 C in CC-CV mode at 45°C until it reached 4.25 V, retrieved, and the formation capacity was measured, after which it was stored in a chamber at 60°C. At weekly intervals, the monocell was removed from the chamber, and the difference between the original weight of the monocell and its weight in water was measured using a hydrometer (MATSUHAKU, TWD-150DM), and the change in volume within the monocell was calculated. The amount of gas generated per unit weight was calculated by dividing the volume change after 4 weeks by the weight of the electrode active material.
[0327] Formation (0 th )Charging capacity (charge; mAh / g) Formation (0 th ) Gas generation amount (mL / g) Cumulative cycle (1 st ~50 th ) Gas generation amount (mL / g) Gas generation amount (mL / g) after 4 weeks at 60℃ Example 1 689 87 3.2 2.7 Example 2 637 81 3.1 3.0 Example 3 649 83 3.0 2.6 Example 4 611 74 3.5 3.0 Example 5 653 84 3.3 2.9 Example 6 621 79 1.8 1.5 Comparative Example 1 640 80 3.6 2.8 Comparative Example 2 755 125 15.0 18.0
[0328] Referring to Table 3 above, the lithium transition metal oxide of Example 1 exhibited the highest charge capacity of 689 mAh / g among the examples, confirming that it can sufficiently compensate for the irreversible capacity loss of the negative electrode. In addition, it was confirmed that using the lithium transition metal oxide of Example 1 resulted in a gas generation level similar to that of Comparative Example 1, enabling the expression of high capacity and excellent safety of the battery.
[0329] In contrast, Comparative Example 2 was found to have significantly reduced battery stability due to the generation of a large amount of oxygen gas, and Comparative Example 1 was found to have insufficient charging capacity.
[0331] Although the present invention has been described above by limited embodiments and drawings, the present invention is not limited thereto, and it is obvious that various modifications and variations are possible within the scope of the technical spirit of the present invention and the equivalent scope of the claims described below by those skilled in the art to which the present invention belongs.
Claims
Claim 1 A lithium (Li)-iron (Fe) oxide containing two or more different heterogeneous elements, wherein the lithium (Li)-iron (Fe) oxide is a lithium transition metal oxide represented by the following chemical formula 1: [Chemical Formula 1]Li5Fe 1-x-y Al x M y O4 In the above chemical formula 1, M is one or more elements selected from the group consisting of magnesium (Mg), fluorine (F), titanium (Ti), zinc (Zn), and gallium (Ga), x is 0.1 to 0.35, and y is 0.01 to 0.
1. Claim 2 delete Claim 3 A lithium transition metal oxide according to claim 1, wherein the heterogeneous element is included in an amount of 5 mol% to 50 mol% based on the total metal elements excluding lithium in the lithium (Li)-iron (Fe) oxide. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 In claim 1, the lithium (Li)-iron (Fe) oxide is Li5Fe 0.82 Al 0.15 Mg 0.03 O4, Li5Fe 0.77 Al 0.2 Mg 0.03 O4, Li5Fe 0.72 Al 0.25 Mg 0.03 O4, Li5Fe 0.81 Al 0.15 Mg 0.04 O4, Li5Fe 0.76 Al 0.2 Mg 0.04 O4, Li5Fe 0.71 Al 0.25 Mg 0.04 O4, Li5Fe 0.82 Al 0.15 F 0.03 O4, Li5Fe 0.77 Al 0.2 F 0.03 O4, Li5Fe 0.72 Al 0.25 F 0.03 O4, Li5Fe 0.81 Al 0.15 F 0.04 O4, Li5Fe 0.76 Al 0.2 F 0.04 O4, Li5Fe 0.71 Al 0.25 F 0.04 O4, Li5Fe 0.82 Al 0.15 Ti 0.03 O4, Li5Fe 0.77 Al 0.2 Ti 0.03 O4, Li5Fe 0.72 Al 0.25 Ti 0.03 O4, Li5Fe 0.81 Al 0.15 Ti 0.04 O4, Li5Fe 0.76 Al 0.2 Ti 0.04 O4, Li5Fe 0.71 Al 0.25 Ti 0.04 O4, Li5Fe 0.82 Al 0.15 Zn 0.03 O4, Li5Fe 0.77 Al 0.2 Zn 0.03 O4, Li5Fe 0.72 Al 0.25 Zn 0.03 O4, Li5Fe 0.81 Al 0.15 Zn 0.04 O4, Li5Fe 0.76 Al 0.2 Zn 0.04 O4, Li5Fe 0.71 Al 0.25 Zn 0.04 O4, Li5Fe 0.82 Al 0.15 Ga 0.03 O4, Li5Fe 0.77 Al 0.2 Ga 0.03 O4, Li5Fe 0.72 Al 0.25 Ga 0.03 O4, Li5Fe 0.81 Al 0.15 Ga 0.04 O4, Li5Fe 0.76 Al 0.2 Ga 0.04 O4 and Li5Fe 0.71 Al 0.25 Ga 0.04 A lithium transition metal oxide, which is one or more compounds selected from the group consisting of O4. Claim 8 A lithium transition metal oxide according to claim 1, wherein the heterogeneous element forms an alloy with iron (Fe) in the lithium (Li)-iron (Fe) oxide and exhibits a single phase as a result of XRD analysis. Claim 9 A lithium transition metal oxide according to claim 1, comprising particles of the lithium (Li)-iron (Fe) oxide and a carbon nanotube-containing carbon composite formed on the particles. Claim 10 A method for manufacturing a lithium transition metal oxide, comprising: a first step of mixing a lithium precursor, an iron precursor, and a heterogeneous element precursor; and a second step of calcining the mixture obtained in the first step under an inert atmosphere and at a temperature of 500°C or higher to obtain a lithium transition metal oxide according to claim 1. Claim 11 A method for manufacturing a lithium transition metal oxide according to claim 10, comprising the steps of: mixing and heat-treating a carbon nanotube and an iron precursor to form an iron oxide-carbon nanotube precursor; and mixing a lithium precursor, a heterogeneous element precursor and the iron oxide-carbon nanotube precursor and calcining at a temperature of 500°C or higher. Claim 12 A method for manufacturing a lithium transition metal oxide according to claim 10, wherein the lithium precursor is a lithium oxide, the iron precursor is one or more compounds selected from the group consisting of chlorides, nitrates, sulfur oxides, phosphoric acids, oxides, halides, and hydrates of Fe(III), and the heterogeneous element precursor comprises an oxide or ammonium salt of a heterogeneous element. Claim 13 A positive electrode additive for a lithium secondary battery comprising a lithium transition metal oxide according to claim 1. Claim 14 A positive electrode for a lithium secondary battery comprising a positive electrode active material, a binder, a conductive material, and a lithium transition metal oxide according to claim 1. Claim 15 A lithium secondary battery comprising a positive electrode; a negative electrode; a separator; and an electrolyte according to claim 14. Claim 16 A lithium secondary battery comprising: a positive electrode according to claim 14; a negative electrode comprising one or more negative active materials selected from the group consisting of carbonaceous materials and silicon compounds; a separator; and an electrolyte.
Citation Information
Patent Citations
Modified lithium iron phosphate positive electrode material and preparation method thereof, positive plate and lithium secondary battery
CN109390563A
